Sleeve video-assisted thoracic surgery resections - Tosi, Davide; Musso, Valeria; Damarco, Francesco; Mohamed, Shehab; Mazzucco, Alessandra; Cattaneo, Margherita; Daffrè, Elisa; Diotti, Cristina; Pieropan, Sara; Nosotti, Mario (Current Challenges in Thoracic Surgery; Vol 2 (May 2020): Current Challenges in Thoracic Surgery, 2020)
Lung resections with bronchoplastic techniques play an important role in the preservation of lung function, in patients with centrally located tumors. Several studies reported oncological outcomes after sleeve resections comparable to pneumonectomy, with lower postoperative mortality and morbidity. Sleeve lobectomy is now considered the procedure of choice for anatomically suitable lesions, regardless of pulmonary function, but is still considered a challenging and technically demanding procedure, especially when carried out by video-assisted thoracic surgery (VATS) approach. The aim of this review article is to describe indications, technical aspects and outcomes of VATS sleeve resections.